Force pattern in roofing system due to wind load - Nadia Faira , Mat Zali (2010)
Recently there are numbers of records regarding damages of the roofing system in Malaysia due to windstorm. In order to avoid the loss of properties a study had been carried out to avoid damages. The objective of this study is to determine the force pattern in roofing system due to wind load. To resist windstorm wind tunnel testing data are used to examine the roofing system. Result from the study showed that the forces that react to the roof are large in shear force rather than tension force (uplift force). From the results, it can be conclude that roofing system need to be strengthen to resist the shear force. Unfortunately, most designer neglected this factor. Hence, to avoid damages to the roofing system, a guideline in using bolt connection in roofing system had been produced in this study.